Boh's pharmacy practice manual : a guide to the clinical experience - Stein, Susan M. (Philadelphia, Pennsylvania : Wolters Kluwer Health, 2015)
Provides a wealth of crucial information for new practitioners. This title features: new color format that makes educational images pop; new table of contents presenting better structural organization: text is streamlined and efficient; textual updates reflect practice and market changes; and expanded calculation coverage.
Professionalism in pharmacy -- Patient safety -- The law and the clinical practice of pharmacy -- Patient consultation in the cycle of patient care -- Providing drug information -- Physical examination -- Interpretation of clinical laboratory test results -- Diagnostic procedures -- Drug administration -- Fluid and electrolyte therapy -- Enteral nutrition -- Parenteral nutrition -- Pharmacy calculations -- Clinical pharmacokinetics -- Clinical drug monitoring -- Antibiotics, antivirals, and infection -- Home test kits and monitoring devices -- Pain management -- Over-the-counter drug therapy and dietary supplements/complementary care -- Vaccines and pharmacists as immunizers
Includes bibliographical references and index.
Keywords: PHARMACY SERVICE, HOSPITAL -- METHODS -- HANDBOOKS